GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT MENGENAI PENANGANAN AWAL PADA LUKA BAKAR DI DESA ARIATE KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT - Yaustien Shenny Tauran; Is Ikhsan Hataul; Stefanus Cahyo Ariwicaksono (Fakultas Kedokteran Universitas Pattimura, 2023)
Burns are tissue damage to the skin caused by sunlight, hot liquids, fire, electricity, and chemicals. Lack of public knowledge about the initial treatment of burns causes the initial treatment of burns to be less precise. The purpose of this study was to describe the level of public knowledge regarding the initial treatment of burns in Ariate Village, Huamual District, West Seram Regency. This research is a descriptive quantitative research design that uses a cross-sectional design. The population of this research is all people who live in Ariate Village, Huamual District, West Seram Regency, with a sampling technique that is simple random sampling. This study uses questionnaire data filled out by respondents and then tabulated; coding, entry, and cleaning; then analysis is carried out on the results of the data. The results of this study obtained an overview of the level of knowledge of the people of Ariate Village, including the sufficient category and the good category, with a percentage of 84.5% consisting of 44% for the sufficient category and 40.5% for the good category. Through this research, it is suggested that there should be socialization efforts from health workers/offices to the community to increase people's knowledge about the initial management of burns.